La cartera vencida y el plan de Riesgo Crediticio para disminuir la morosidad de los socios de la Cooperativa de Ahorro y Crédito Inti Ñan Ltda. de la parroquia Guanujo del cantón Guaranda en el año 2013 - Acurio Mendoza, Alex Joselo (2014)
The graduation paper aims to propose a plan of Risk, the same that is based on strict policies, allowing to analyze and recover NPLs and reduce delinquencies Cooperative Savings and Credit "Nan INTI" Ltda. During the year 2013 to improve lending processes and meet corporate objectives. First reference to the background where it is stated that the Cooperative Savings and Credit "Inti Nan" Ltda., Has a high rate of delinquency due to lack of credit policies, in justifying the significance discussed is the need, the feasibility of the work, besides the objectives to be achieved as well by the hypothesis that seeks to provide an alternative solution to the problem is proposed. This work is typified by gradation chapters. Chapter I contains the theoretical framework within which the guiding framework detailing all information of the institution in which the study was discussed, we also find a sketch showing the exact location of the institution; The legal framework provides for the legal basis of the investigation carried out in the Framework the basics that have been used within the independent and dependent variables is defined, and the scientific theory relevant content gathered through books and the internet is exposed respect the NPLs, delinquencies and risk plan. Chapter II contains the analysis and interpretation of results where it is described by tables and charts on the results of the application survey to members who belong to the institution, and the hypothesis is tested by the formula Chi Square and presents the conclusions and recommendations to solve the existing problem. Chapter III contains the development of the Proposal which is by the same policies that allows us to establish the Credit Risk Plan for Cooperative Savings and Credit "Inti Nan" Ltda. It provides an alternative solution also expressed the desired results.